Associations between hippocampal morphology, diffusion characteristics, and salivary cortisol in older men. (April 2017) - Cox, Simon R.; Valdés Hernández, Maria del Carmen; Kim, Jaeil; Royle, Natalie A.; MacPherson, Sarah E.; Ferguson, Karen J.; Muñoz Maniega, Susana; Anblagan, Devasuda; Aribisala, Benjamin S.; Bastin, Mark E.; Park, Jinah; Starr, John M.; et al.
Highlights: Elevated cortisol does not appear to be associated with regional variations in hippocampal shape. Novel shape morphology analysis applied to study possible effect of cortisol on hippocampus. Mean diffusivity in hippocampus is associated with reactive cortisol slope in older men. Abstract: High, unabated glucocorticoid (GC) levels are thought to selectively damage certain tissue types. The hippocampus is thought to be particularly susceptible to such effects, and though findings from animal models and human patients provide some support for this hypothesis, evidence for associations between elevated GCs and lower hippocampal volumes in older age (when GC levels are at greater risk of dysregulation) is inconclusive. To address the possibility that the effects of GCs in non-pathological ageing may be too subtle for gross volumetry to reliably detect, we analyse associations between salivary cortisol (diurnal and reactive measures), hippocampal morphology and diffusion characteristics in 88 males, aged ∼73 years. However, our results provide only weak support for this hypothesis. Though nominally significant peaks in morphology were found in both hippocampi across all salivary cortisol measures (standardised β magnitudes < 0.518, puncorrected  > 0.0000003), associations were both positive and negative, and none survived false discovery rate correction. We found one single significant association (out of 12 comparisons) between a general measure of hippocampal diffusion and reactive cortisol slope ( β   =  0.290, p  = 0.008) which appeared to be driven predominantly by mean diffusivity but did not survive correction for multiple testing. The current data therefore do not clearly support the hypothesis that elevated cortisol levels are associated with subtle variations in hippocampal shape or microstructure in non-pathological older age.